Peran TP4D Kejaksaan Negeri Denpasar dalam Mengawal Pembangunan Daerah dalam Pencegahan Tindak Pidana Korupsi - Ni Ketut Puput Cahyaningsih; I Gusti Bagus Suryawan; I Nengah Laba (Warmadewa Press, 2021)
The implementation of strategic policies to eradicate corruption through prosecution alone will not succeed without the prevention efforts as a form of awareness for the public about the dangers of corruption which ultimately arouse the spirit of anti-corruption in all levels of society. Attorney General's instruction Number: INS-001 / JA / 10/2015 concerning the establishment and implementation of the duties of the guards for the security of the central and regional government, the formation of the TP4D Team was intended for safeguarding and escorting the government in the execution of strategic projects to be successful and to prevent corruption. This research uses juridical empirical methods and purposive techniques. Data analysis of this research was carried out qualitatively. The problems in this research are about (1) What is the role of the The authority of the Guard, Government and Regional Development Team (TP4D) in Denpasar District Prosecutor’s an effort to prevent corruption? (2) What obstacles have been faced The authority of the Guard, Government and Regional Development Team (TP4D) Denpasar District Prosecutor’s in guarding regional development? Based on the results of interviews with the Head of Intelligence Section, Head of Financial Economic and Strategic Development Sub-Section and Head of the Investigation Section it can be conclude: (1) The Role of Denpasar District Prosecutor’s in preventing corruption includes providing legal opinions on the running of local government development projects to anticipate abuse of power (2) the obstacles experienced by the TP4D Denpasar District Prosecutor’s in guarding development in the city of Denpasar there are two obstacles including technical barriers and judicial barriers.